2018
DOI: 10.1186/s12969-018-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of survival rates in the last decade in Thai childhood-onset systemic lupus erythematosus

Abstract: BackgroundMorbidity and mortality in childhood onset systemic lupus erythematosus (SLE) is more severe than adult onset SLE. Long-term follow up is needed to determine the prognosis. The objectives of this study are to describe the mortality of childhood SLE in a single tertiary care centre over three decades, compare trends in survival over time, and determine predictors for survival.MethodsWe retrospectively reviewed the medical records of children aged < 18 years who were diagnosed with SLE at the Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…However, a more recent study showed marked improvement in survival with the country’s economic development and accessibility to healthcare with a mortality of only 1.6% in a 5-year cohort on par with other developed countries in the world [ 29 , 47 , 48 ]. Mortality rates in Thailand (23.3–31.2%) remain high despite improvement over the years with most deaths occurring within the first year of presentation [ 49 , 50 ]. Dung et al reported similar findings of high incidence of early deaths in 8.9% of their cohort in Vietnam within the first six months of diagnosis [ 19 ].…”
Section: Disease Activity Disease Damage Long-term Outcomes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a more recent study showed marked improvement in survival with the country’s economic development and accessibility to healthcare with a mortality of only 1.6% in a 5-year cohort on par with other developed countries in the world [ 29 , 47 , 48 ]. Mortality rates in Thailand (23.3–31.2%) remain high despite improvement over the years with most deaths occurring within the first year of presentation [ 49 , 50 ]. Dung et al reported similar findings of high incidence of early deaths in 8.9% of their cohort in Vietnam within the first six months of diagnosis [ 19 ].…”
Section: Disease Activity Disease Damage Long-term Outcomes Andmentioning
confidence: 99%
“…Dung et al reported similar findings of high incidence of early deaths in 8.9% of their cohort in Vietnam within the first six months of diagnosis [ 19 ]. These could reflect the high prevalence of renal disease in these countries with poor healthcare accessibility, delayed diagnosis, and limited paediatric rheumatology expertise [ 45 , 49 ]. Meanwhile, the mortality rates of 7.6% (5-year follow-up) in the Philippines and 5.7% (10 year follow up) in Malaysia are comparable to other developed countries [ 21 , 24 ].…”
Section: Disease Activity Disease Damage Long-term Outcomes Andmentioning
confidence: 99%
“…There is also a markedly increased risk of cardiovascular disease in adulthood [ 84 , 85 ]. Ten-year survival for JSLE in LRIC and MRIC is approximately 80% [ 2 , 80 , [86] , [87] , [88] , [89] , [90] ] compared with 99% in HRIC [ 85 ], with lupus nephritis and infection, the major causes of death [ 91 , 92 ].…”
Section: Impact Described Through Selected Msk Conditionsmentioning
confidence: 99%
“…Despite a general lack of comorbid conditions, previous studies have shown that patients with childhood SLE are at a greater risk of mortality compared to patients with adult SLE, and especially those with LN 12,13 . With earlier recognition of the disease, increased availability of new immunosuppressants and improved intensive care, the 5-year and 10-year survival rates for childhood SLE have improved considerably in the last decade 14 . As survival rates for childhood SLE have improved, prevention and early treatment of morbidities resulting from disease activity and adverse effects of treatment, and especially corticosteroids and immunosuppressants, have become increasingly important.…”
Section: Discussionmentioning
confidence: 99%